Indigenous Economic Development Education: Aligning Curriculum with Community Aspirations - Brooks, Tasha; Gowans, Sarah (Journal of Aboriginal Economic Development, 2025)
This research examines how postsecondary economic development curricula can align with the needs of Indigenous communities in Canada. Drawing on Indigenous research principles and mixed methods design, the study combines a literature review with semi-structured interviews (n=17) and an online survey (n=43) of Indigenous economic development practitioners and prospective students. Key curriculum priorities include leadership, governance, financial literacy, cultural competency, Indigenous knowledge systems, entrepreneurship and business skills, and legal and regulatory frameworks. Participants emphasized the central role of Indigenous economic development corporations; the importance of meaningful employment and revenue generation for community well-being; and the need to embed Elders, Indigenous instructors, and Indigenous knowledge. The findings support flexible program structures that allow students to maintain employment while participating in online learning with short in-person residency components. Overall, the study provides early guidance for designing culturally grounded economic development education that supports Indigenous self-determination, builds local capacity, and contributes to sustainable economies.